Hemangiopericytoma: Conducts and perioperative management of an extent sinonasal tumor in a Jehovah's Witnesses patient ‐ Case report - Francisco S. Amorim Filho; Flávio M. Gripp; Guilherme S. Faria; Mateus Capuzzo Gonçalves; Lincoln Miyahira (Cancer Reports, 2022)
Abstract Background Hemangiopericytomas (HPCs) are rare tumors derived from mesenchymal cells with pericyte differentiation. About 5% of head and neck HPCs occur in the nasal cavity and paranasal sinuses. Due to its rarity, rich vascularity and variable biological behavior, its management is a challenge in itself. Case We report a case of sinonasal HPC in a Jehovah's Witness patient and discuss the obstacles and care related to the restrictions and therapeutic challenges involved in the approach to the patient. The patient was successfully treated by endoscopic endonasal approach with all per‐operative care and restrictions being respected and attended. Conclusions The management of HPC by itself involves challenges and when associated with other restrictive conditions attention and care are required.